pHMA, a pH-sensitive GFP reporter for cell engulfment in Drosophila embryos, tissues and cells - Fishilevich, Elane (2010)
Engulfment of apoptotic cells by phagocytosis ensures the removal of unwanted and defective cells. We developed a genetically encoded marker for cell engulfment, pHMA, which consists of the pH-sensitive derivative of GFP, pHluorin, fused to the actin-binding domain of Moesin. In healthy cells of Drosophila embryos and cultured cells, pHMA resides at the cell cortex. In dying cells, pHMA loses its cortical localization and reports a modest decrease in pH. In embryos, the dying cells lose their apical contacts, then move basally and are ultimately engulfed by neighboring cells or macrophages. The cell corpse material is strongly acidified soon after engulfment and persists in the phagocytic cell for several hours. Changes in the pHMA signal correlate well with increases or decreases in apoptosis. These data show that pHMA is a useful reporter for cell engulfment and can be used in screening for mutations that affect cell engulfment.